Il Milione. The first 14 years of ERC funding to human past studies (SH6): an Italian perspective - Lago, Giancarlo; Di Renzoni, Andrea (Ex Novo: Journal of Archaeology, 2021)
This article addresses European Research Council (ERC) grants in the Archaeology and History panel (SH6). The study was conducted by considering the first two cycles of ERC funding (2007-2020). We introduce to eligibility criteria and evaluation process involved in ERC calls. We show the results of the analysis in terms of most awarded ‘countries’ per call (Starting Grant, Consolidator Grant, Advanced Grant), the profiles of researchers and the main research subjects of 360 granted funding. The inquire is extended to a systematic analysis regarding the profile of scientific members of the commissions (480 scholars) employed to evaluate the proposals. The outcome is that Italian institutions underperforming compared to other major European countries; the success rate of ‘Italian’ proposals is lower than the European average; young Italian researchers very rarely obtain Starting Grants. This is, we believe, partly due to some policies currently still in place – even if no longer sustainable - in Italian universities. There is some correlation between most awarded institutions (by country) and most employed panelists. In the final part, we show the main trending topics of ERC projects.